Determinants of Creative Industry in Financial Reporting - Fitriyani, Dewi; Yuliusman; Mansur , Fitrini; PrasetyoPrasetyo, Eko (International Journal of Psychosocial Rehabilitation, 2020)
Financial statements are accounting information that can be used by entrepreneurs to determine the condition and financial performance. Financial statements are also a form of financial management accountability. Important for entrepreneurs to prepare financial statements. Therefore this study aims to determine the factors that influence the creative industries in preparing financial statements. The factors examined include the latest level of education, educational background, business size, length of business, banking financing, and understanding of accounting. The study was conducted in the creative industry in the field of printing in Jambi City. Data were collected by survey method using a questionnaire. The hypothesis was tested using logistic regression method. The results showed that the size of the business, banking financing and understanding of accounting affect the creative industry to prepare financial reports, while the level of education, educational background, and length of business standing have no effect. this research can be beneficial for the government in developing creative industries. the government needs to increase the understanding of creative industry entrepreneurs in accounting to raise awareness and ability of creative industries in preparing financial reports.